An Experimental Evaluation of The Effects of Relative Draft and Centre of Gravity Position on The Performance Wave Energy Converter - Noh Zainal Abidin; Mohd Rashdan Saad; Mohd Rosdzimin Abdul Rahman; Mohd Norsyarizad Razali; Ameer Suhel; Mohamad Azrin Abd Azis; Mohd Najib Abdul Ghani Yolhamid; Zulkifly Mat Radzi (International Journal of Integrated Engineering, 2025)
Prior studies highlight that the Backward Bent Duct Buoy (BBDB) is one of the simplest and most robust wave energy converters (WECs). However, the impact of relative draft and the location of the center of gravity (COG) on the hydrodynamic performance of the BBDB remains inconsistent and underexplored in the field. Thus, this study investigates the optimal relative draft and center of gravity (COG) location for maximizing the hydrodynamic performance of the Backward Bent Duct Buoy (BBDB), a simple and robust wave energy converter. The research explores the influence of different drafts and COG locations across wave heights (0.03 m, 0.04 m, 0.05 m) and periods (1s to 2s) using the OMEY's flume wave tank. A Froude scale of 1:13 was applied to the BBDB model. Verification and validation with previous studies yielded a percentage difference of 0.22%. Results show that a draft of T=0.3m (T/D=0.53) with an upright COG achieves the highest conversion efficiency of 56.7% at a wave height of 0.05 m, outperforming other configurations. Lower efficiency of 16.1% was noted for the Port COG at H=0.03m. The T=0.3m draft with the exact COG maximizes heave and pitch oscillations, enhancing internal air pressure variations and overall energy conversion. Appropriate COG positioning and draft are key to achieving resonance, reducing drag, and improving performance. This study emphasizes the significance of draft and COG location in optimizing BBDB design and operation, particularly in low wave height conditions.